Recognition of the Magnaporthe oryzae Effector AVR-Pia by the Decoy Domain of the Rice NLR Immune Receptor RGA5. Issue 1 (13th January 2017) - Ortiz, Diana; de Guillen, Karine; Cesari, Stella; Chalvon, Véronique; Gracy, Jérome; Padilla, André; Kroj, Thomas
Abstract : The Magnaporthe oryzae effector AVR-Pia interacts with the decoy domain of the rice NLR immune receptor RGA5 through a defined surface area, and this interaction is required for effector recognition. Abstract: Nucleotide binding domain and leucine-rich repeat proteins (NLRs) are important receptors in plant immunity that allow recognition of pathogen effectors. The rice ( Oryza sativa ) NLR RGA5 recognizes the Magnaporthe oryzae effector AVR-Pia through direct interaction. Here, we gained detailed insights into the molecular and structural bases of AVR-Pia-RGA5 interaction and the role of the RATX1 decoy domain of RGA5. NMR titration combined with in vitro and in vivo protein-protein interaction analyses identified the AVR-Pia interaction surface that binds to the RATX1 domain. Structure-informed AVR-Pia mutants showed that, although AVR-Pia associates with additional sites in RGA5, binding to the RATX1 domain is necessary for pathogen recognition but can be of moderate affinity. Therefore, RGA5-mediated resistance is highly resilient to mutations in the effector. We propose a model that explains such robust effector recognition as a consequence, and an advantage, of the combination of integrated decoy domains with additional independent effector-NLR interactions.